PERAN PUSAT PELATIHAN PERTANIAN DAN PEDESAAN SWADAYA GRIYA VANILI DALAM PEBERDAYAAN PETANI VANILI DI SALATIGA - Dicky Isandro Gaspersz; Damara Dinda Nirmalasari Zebua (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The vanilla commodity, which once triumphed in its era in the 1980s, has experienced a decline due to the decline in selling prices in the 1890s. It has resulted in many vanilla farmers switching to other commodities. One of the Independent Agricultural and Rural Training Centers that empowers vanilla farmers is Griya Vanili Salatiga, better known as P4S Griya Vanilla. The aims of this study were 1) to determine the condition of the assisted farmers in P4S Griya Vanili Salatiga; 2) to know the role of P4S Griya Vanili Salatiga towards its fostered farmers. This study involved the Head of P4S Griya Vanili Salatiga as Key Informants and two farmers assisted by P4S Griya Vanili Salatiga as participants. The data were analyzed using an interactive analysis model, including data reduction, presentation, and conclusion. The results showed that: 1) the condition of the farmers assisted by P4S Griya Vanili Salatiga experienced a change in the mindset of vanilla farming, namely from subsistence farmers to commercial farmers; 2) the role of P4S is as a source of increasing knowledge and changing the mindset of farmers through the provision of training materials and infrastructure needed by fostered farmers. P4S Griya Vanili Salatiga has broughtabout significant changes in the agricultural conditions of its fostered farmers, both from the economic and cognitive aspects.